DEVELOPMENT OF RESPIRATORY SYSTEM RPG GAME USING UNITY WITH A* (A STAR) ALGORITHM (Jurnal Pilar Nusa Mandiri, 2024)
This research addresses the need for more engaging and interactive methods to improve elementary students' understanding of complex scientific concepts, particularly the respiratory system. To overcome the limitations of traditional teaching methods, an educational Role-Playing Game (RPG) incorporating the A* (A-Star) algorithm was developed for optimal game navigation. The study followed the ADDIE development model, which involves Analysis, Design, Development, Implementation, and Evaluation. During the analysis phase, learning needs were determined through interviews and classroom observations. The design phase involved creating game scenarios and integrating educational content with interactive elements. The A* algorithm was applied during development to ensure efficient navigation. The game was implemented in a 5th-grade classroom in Kuningan, and its effectiveness was evaluated using pre-tests, post-tests, and student questionnaires. Results demonstrated a significant increase in students' understanding, with average post-test scores rising from 58 to 85. Feedback from both students and teachers was very positive, with the game receiving a 94.2% acceptance rate. The study suggests that RPG-based educational games with intelligent algorithms like A* can greatly enhance science education by offering a more engaging and effective learning experience, contributing to advancements in technology-based learning and setting a standard for future educational game development.